Assessment of Health Care Quality through Clients’ Perspectives at Outpatient Consultancy Clinics in Al-Hilla City Hospitals - Hamzah, Mahdi; Talib, Mahasin (Iraqi National Journal of Nursing Specialties, 2020)
Objectives: To assess quality of health care for clients at outpatient consultancy clinics in Al-Hilla City Hospitals, and to find out significant differences between the clients’ perspectives toward quality of health care dimensions and their demographic characteristics such as (residence, age, gender, level of education, and occupation ). Methodology: A descriptive analytic study design was carried out at outpatient consultancy clinics of Al- Hilla city hospital (Al-Hilla and Al-Imam Al-Sadiq general teaching hospital) from April 10 th to June 15 th 2019. Non – probability (purposive) sample of 200 clients who were coming to the Outpatient Consultancy Clinics were selected. Data is collected through used of an assessment tools and interview technique with (27) items of questionnaire. A pilot study is conducted for the determination of the reliability of the assessment tool through the use of internal consistency reliability through the use of Alpha Cronbach approach(0,85) (p<0.001) and content validity through a panel of (20) experts. Data are analyzed through the application of the Statistical Package of Social Sciences (SPSS, Version 20) was performed through the application of descriptive statistics (frequency, percentage, mean, and cut off point) and inferential statistics (t-test and one way analysis of variance). Results: The study indicates that The overall assessment quality of health care dimension according to SERVQUAL scale at poor level, and There are significant differences in clients’ perspectives for quality of health care with regard to their demographic characteristics of residence, gender, age, level of education, and occupation. Recommendations: Provision of qualified physicians and registered nurses who deals with outpatient consultancy clinics in Al-Hilla city hospitals, and establishment plans of training and development for medical and nursing staff to increase their knowledge, skills, and awareness to quality of health care for their practices that lead to provide best health care for clients.